The Choice of Every Woman - Abu Saif, As-Sayyid bin Ahmad (Darussalam, 2004)
How Islam is defending the rights of women? How Islam raises the status and importance of women in a society? A must read book on the topic of Woman & IslamJust as men have duties that are not binding upon women... such as praying in congregation, providing for one's family, fighting in the way of Allah, etc.; women have duties that are not binding upon men... such as wearing Hijab, raising children while the men are gone out to work, etc. This involves nothing more than a distribution of duties.The choice is with every woman: Will she follow the ideas and morals that are formulated by human beings, whose minds are inherently deficient, or will she follow what her Lord has commanded her to do?